Ultrasonographic Characterization of the db/db Mouse: An Animal Model of Metabolic Abnormalities - Francesco Faita; Nicole Di Lascio; Chiara Rossi; Claudia Kusmic; Anna Solini (Journal of Diabetes Research)
The availability of an animal model able to reliably mirror organ damage occurring in metabolic diseases is an urgent need. These models, mostly rodents, have not been fully characterized in terms of cardiovascular, renal, and hepatic ultrasound parameters, and only sparse values can be found in literature. Aim of this paper is to provide a detailed, noninvasive description of the heart, vessels, liver, and kidneys of the db/db mouse by ultrasound imaging. Sixteen wild type and thirty-four db/db male mice (11-week-old) were studied. State-of-the-art ultrasound technology was used to acquire images of cardiovascular, renal, and hepatic districts. A set of parameters describing function of the selected organs was evaluated. db/db mice are characterized by systolic and diastolic dysfunction, confirmed by strain analysis. Abdominal aortic and carotid stiffness do not seem to be increased in diabetic rodents; furthermore, they are characterized by a smaller mean diameter for both vessels. Renal microcirculation is significantly compromised, while liver steatosis is only slightly higher in db/db mice than in controls. We offer here for the first time an in vivo detailed ultrasonographic characterization of the db/db mouse, providing a useful tool for a thoughtful choice of the right rodent model for any experimental design.